History of Islam in Australia: Muslim Migration and the Evolution of Islamic Education - Jaelani; Irwan; Ratisa; Yesi (Jurnal Ilmiah Edukatif, 2024)
This study describes the history of Islam in Australia, highlighting the influx of Muslims and depicting the development of Islam in the country. This research employs the historical method, comprising four stages: heuristics for source collection, source verification or criticism, interpretation or analysis, and historiography for historical writing. The results of this study demonstrate that Islam began to spread to Australia in the early 17th century, primarily due to the regular presence of Makassar fishermen and traders searching for tripang. The next wave of Muslims who came and settled in Australia were Afghan Muslims, Malay Muslims, Indians, Albanians, Lebanese, Indonesians, and so on. The presence of Islam encourages Islamic education in the country, starting with non-formal Islamic education centered in mosques, homes, or offices of Islamic organizations. Various Muslim communities conduct studies and seminars on weekends, commonly known as 'Saturday or Sunday School.' The 1970s saw the establishment of formal Islamic schools in response to the growing Muslim population. The development of Islamic education in Australia gained momentum in the mid-1990s. Privately run Islamic schools adopt the entire local education system, with an additional six hours per week for religious content. As Islamic schools have developed, they have expanded to various states in Australia. The attitude of tolerance and openness that Islamic schools in Australia cultivate supports this